1. Predicting the value of standing trees through quality inventory: a case study of Meranti trees (Shorea sp.) in Province of Jambi, Indonesia - Sitti Latifah (JURNAL AGRIMANSION, 2007)
Abstract The value of trees depends not only on dimension and price but also on its quality. Until now, the estimation of tree value is still done when the tree has already felled. This condition caused only certain quality of wood will be extracted. This study tried to correlate the dimension of standing tree, which is easy to measure, and its economic value. Quality inventory method was implemented on standing trees. The result shows that basically the value of standing tree can be estimated through its dimension which has already included the quality on it. Abstrak Nilai ekonomis suatu pohon tidak hanya ditentukan oleh dimensi dan harganya tetapi sangat ditentukan pula oleh kualitasnya. Selama ini, penentuan nilai pohon hanya dilakukan ketika pohon telah rebah. Hal tersebut yang menyebabkan kayu dengan kualitas tertentu saja yang diekstrak ke luar hutan. Penelitian ini mencoba menghubungkan antara dimensi pohon berdiri yang mudah untuk diukur dengan nilai ekonomisnya. Metode invetarisasi kualitas pada pohon berdiri dicobakan pada penelitian ini. Hasil menunjukkan bahwa ternyata nilai satu pohon berdiri dapat diduga melalui dimensinya yang telah memasukkan unsur kualitas didalamnya.